Una polilla Lepidoptera, Gelechiidae sobre trébol de olor blanco Melilotus alba - Pagnone, T.; Martínez, A. (Semiárida, 2020)
Una polilla Lepidoptera, Gelechiidae sobre trébol de olor blanco Melilotus alba